Entre régionalisme et régionalisation, le difficile positionnement du Norden en Europe - Jacques Guillaume (Belgeo)
After defining the terms on which this paper is based, the author describes the foundations of Norden’s unity that depend on cultural and political categories to be classified in regionalism. Nevertheless, he suggests also their limitations, which are partly related to strong external and economic polarizations, linked to regionalization process and revealed by the European integration. Geographical factors of explanation are mentioned in the third part of this paper.